2019
DOI: 10.1038/s41598-019-52312-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression profiles and positive selection analysis in the tree swallow (Tachycineta bicolor) using a de novo transcriptome assembly

Abstract: Tree swallows (Tachycineta bicolor) are one of the most commonly studied wild birds in North America. They have advanced numerous research areas, including life history, physiology, and organismal responses to global change; however, transcriptomic resources are scarce. To further advance the utility of this system for biologists across disciplines, we generated a transcriptome for the tree swallow using six tissues (brain, blood, ovary, spleen, liver, and muscle) collected from breeding females. We de novo as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 98 publications
(121 reference statements)
6
19
0
Order By: Relevance
“…Another possibility in such a situation is to assemble a transcriptome de novo without the need to rely on genetic information from a related species as has been demonstrated in other studies ( Vijay et al. 2013 ; Bentz et al. 2019b ).…”
Section: Behavioral Plasticitymentioning
confidence: 99%
“…Another possibility in such a situation is to assemble a transcriptome de novo without the need to rely on genetic information from a related species as has been demonstrated in other studies ( Vijay et al. 2013 ; Bentz et al. 2019b ).…”
Section: Behavioral Plasticitymentioning
confidence: 99%
“…In addition, it is important to highlight that there are genes with tissue-specific expressions, which are under specific regulation, as reported by Bentz et al [41], who found differential genes expression among tissues in swallows. For example, muscle-specific genes were associated with muscle contraction, and spleen-specific genes with immune response.…”
Section: Genesmentioning
confidence: 91%
“…Tissue-selective gene expression is an important mechanism by which the same genome can generate differentiated phenotypes among tissues (Bentz et al 2019). Exploring the pathologic consequences of human genes in specific tissues is typically more essential for insights into disease diagnostics and therapeutics (Barbeira et al 2018;Hekselman and Yeger-Lotem 2020).…”
Section: Predicting Protein-phenotype Associations Under the Specific Mechanismsmentioning
confidence: 99%